Optimization of DNA Extraction and RAPD Protocols for Dry Capsicum Seeds - Batista, Enrico Diniz Rodrigues; Bertão, Mônica Rosa [UNESP]; Palmieri, Darío Abel [UNESP]; Zaniboni, Camila Baptistão; Moraes, Milena Cristina [UNESP] (FapUNIFESP (SciELO), 2024)
Genetic analyses through molecular markers always depend on efficient protocols for DNA extraction and standardized PCR conditions. Random Amplified Polymorphic DNA (RAPD) is an inexpensive protocol that can provide information about the genetic diversity among Capsicum accessions within a germplasm bank, but it is highly sensitive to reaction conditions and manipulation. This work presents an optimized protocol for DNA isolation from dry Capsicum seeds, and a standardization of five conditions for PCR using RAPD primers. The RAPD protocol was optimized for the following parameters: 50 ng of DNA template per mix, 2.5 mM MgCl2, 200 μM dNTP's, 25 ng of primer per mix, and 45 thermal cycles, resulting in reproducible and clear amplified fragments. Good quality products were presented in the extractions and amplifications carried out; therefore, the optimized protocols are sufficient to be used in future work with RAPD.
Keywords: DNA isolation; Molecular analysis; PCR; Pepper; Primer